The Influence of Ventilation Arrangement on the Mechanism of Dust Distribution in Woxi Pithead - Zhiyong Zhou; Pei Hu; Chongchong Qi; Tianpei Niu; Ming Li; Long Tian (Shock and Vibration)
Suppressing and removing mine dust from the working face is an important task for underground mines worldwide. In this paper, a numerical study was carried out to investigate the influence of ventilation arrangement on the mechanism of dust distribution. The Woxi Pithead of Hunan Chenzhou Mining Co., Ltd, China, was used as a case study, which adopted a widely used far-pressing-near-absorption (FPNA) ventilation system. Based on the theory of gas-solid two-phase flow, the program ANSYS Fluent was utilized, and the three-dimensional airflow migration and dust diffusion numerical models were simulated. The established computational fluid dynamics (CFD) models were validated using the airflow velocity data and the dust concentration data monitored at different positions from the operating coal mine. A comprehensive sensitivity study was conducted to investigate the influence of four parameters on dust suppression, including the distance of pressure air duct outlet from working face (Lp-outlet), the distance of exhaust air duct inlet from working face (Le-inlet), the ratio of pressing air volume to lab sorption air volume (K), and the installation height of the air duct (H). The optimum ventilation layout parameters were obtained through the simulation of the wind field and dust behaviour. The results show that there were four regions during the airflow field, namely, the jet zone, the recirculation zone, the vortex zone, and the mixing zone of pressure and exhaust airflow. All four parameters were found to have an important influence on the mass concentration of dust, and the optimum ventilation layout parameters were determined to be Lp-outlet = 18 m, Le-inlet = 3 m, K = 1.2, and H = 1.6 m.